An Overview of Approaches to Nuclear Security in Ghana - Raymond Agalga; Paul Atta Amoah; Daniel Nii Adjei; Daniel Frederick Charles; Emmanuel Ofori Darko (International Journal of Nuclear Security, 2022)
Ghana has significantly improved its nuclear security infrastructure over the years. However, as threats increase by the day and new applications of nuclear and radiological technology are designed and implemented, Ghana must develop a rigid and comprehensive approach to mitigating the negative impacts on its nuclear security while improving prevention, detection, and deterrence of nuclear and radiological terrorism within its geographical space. This paper overviews the approaches adopted by Ghana to build a strong nuclear security regime within the past decade. These include improving legal frameworks for nuclear security by establishing an independent Nuclear Regulatory Authority; assessing nuclear security culture in facilities; strengthening nuclear security capabilities at facilities that hold radioactive materials by improving physical protection systems for deterrence and detection; and building strong and effective collaboration and cooperation with various stakeholders, both locally and internationally, to distribute responsibility and provide technical and logistic support to build a stronger nuclear security regime. Ghana also identified developments in human capacity in areas of nuclear security as a relevant approach to improving its nuclear security and has thus collaborated with the IAEA and the University of Ghana to establish a graduate school for training Ghanaians and Africans in nuclear-related disciplines.
Keywords: Nuclear Security; Cooperation; Nuclear Security Regime; Ghana